Viruses hijack FPN1 to disrupt iron withholding and suppress host defense - Li Tong; Jie Wang; Yunjin Ma; Chunying Wang; Yue Fu; Qi Li; Chengjiang Gao; Hui Song; Ying Qin; Chunyuan Zhao; Wei Zhao (Nature Communications)
Abstract Viruses rely on intracellular materials, including iron, to complete their life cycles and iron withholding may limit viral infections. However, the mechanisms through which viruses disrupt host iron homeostasis and the impact of intracellular iron on the host’s antiviral defense aren’t well studied. Here we show that viral infections facilitate the polyubiquitination and degradation of ferroportin (FPN1, the only cellular iron exporter) by upregulating the host E3 ubiquitin ligase DTX3L, leading to an elevation in cellular iron levels. Excessive ferrous iron suppresses type I IFN responses and autophagy by promoting TBK1 hydroxylation and STING carbonylation in macrophages. FPN1 deficiency suppresses host antiviral defense and facilitates viral replication in vitro and in vivo, while DTX3L deficiency has the opposite effect. These results reveal that viruses hijack host FPN1 to disrupt iron withholding and achieve immune escape, and suggest that iron homeostasis maintained by FPN1 is required for the optimal activation of TBK1- and STING-dependent antiviral responses.